Progressive leadership in strengthening teacher professionalism at SMK Muhammadiyah 1 Baturetno - Wijayanti, Rochmah; Prayitno, Harun Joko; Sumardjoko, Bambang (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the role of the principal's progressive leadership in strengthening teacher professionalism at SMK Muhammadiyah 1 Baturetno. This study used a qualitative approach with a case study design. Data collection was conducted through in-depth interviews with the principal and teachers, observations of learning activities and teacher collaborative forums, and documentation studies. Data analysis was carried out interactively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the progressive leadership implemented by the principal is reflected in participatory, humanistic, and empowerment-oriented leadership practices. The main strategies found include teacher involvement in decision-making, reflective learning mentoring, and support for innovation and collaboration between teachers. These practices contribute positively to increasing teacher commitment, responsibility, and courage in developing innovative and meaningful learning. This study concludes that teacher professionalism is not only built through formal supervision, but also through dialogic and collaborative leadership relationships. Progressive leadership can be an alternative model of school leadership in improving the quality of learning, especially in vocational schools based on Islamic values.